Oxidation behavior of STA β-21S alloy and variants [Ti-xNb-yMo-5.6Al-0.5Si at%; x + y = 9.5]. (15th July 2022) - Ferreira, L.M.; Chaia, N.; Coelho, G.C.; Nunes, C.A.
Abstract: A correlation between the Nb/Mo contents in the β-21S alloy and the oxidation behavior at high temperatures was investigated. Five alloys were oxidized pseudo-isothermally at 700, 750 and 800 °C under static lab air for long periods. The kinetics of mass change versus time follow a parabolic law. Oxygen dissolution in the substrate represent the main part of the mass uptake. The increase of the Nb content in the alloys induces the formation of TiN and the reduction of the TiO2 scale. The results showed also that microstructural changes associated with the increase in temperature strongly affect the oxidation behavior. Graphical Abstract: ga1 Highlights: Nb contribute to stabilize a continuous TiN layer that act as diffusion barrier. The oxygen dissolution represents the main part of the mass changes. Oxygen ingress into the substrates depends on microstructural features of the alloy.